2017
DOI: 10.3847/1538-4357/aa890b
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Solar Fine Structure Observed Simultaneously in Lyα and Mg ii h

Abstract: The Chromospheric Lyman Alpha Spectropolarimeter (CLASP) observed the Sun in H I Lyα during a suborbital rocket flight on 2015 September 3. The Interface Region Imaging Telescope (IRIS) coordinated with the CLASP observations and recorded nearly simultaneous and co-spatial observations in the Mg II h and k lines. The Mg II h and Lyα lines are important transitions, energetically and diagnostically, in the chromosphere. The canonical solar atmosphere model predicts that these lines form in close proximity to ea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The main problem in modeling both long fibrils and flare ribbons is that the radiation originating from the solar chromosphere forms under complex non-Local Thermodynamic Equilibrium (non-LTE) conditions. On the one hand, this makes observations of the chromosphere difficult to interpret; on the other hand, the forward synthesis of chromospheric lines becomes quite complex and computationally expensive (Leenaarts et al 2012;Štěpán et al 2015;Schmit et al 2017;Leenaarts et al 2013b;Bjørgen et al 2018;Sukhorukov & Leenaarts 2017) if one wants to reproduce the spectral lines in detail.…”
Section: Introductionmentioning
confidence: 99%
“…The main problem in modeling both long fibrils and flare ribbons is that the radiation originating from the solar chromosphere forms under complex non-Local Thermodynamic Equilibrium (non-LTE) conditions. On the one hand, this makes observations of the chromosphere difficult to interpret; on the other hand, the forward synthesis of chromospheric lines becomes quite complex and computationally expensive (Leenaarts et al 2012;Štěpán et al 2015;Schmit et al 2017;Leenaarts et al 2013b;Bjørgen et al 2018;Sukhorukov & Leenaarts 2017) if one wants to reproduce the spectral lines in detail.…”
Section: Introductionmentioning
confidence: 99%
“…The line center is formed around the transition region while the line wings are formed in the mid-chromosphere (Vernazza et al 1981). Schmit et al (2017) studied the correlation of the Lyα line with the Mg II h line which is formed in the mid-upper chromosphere. They found that for both observations and simulations, there is a good correlation between the core intensities of the two lines.…”
Section: Introductionmentioning
confidence: 99%
“…Bjørgen et al (2018) use similar models to study the formation of the Ca ii H and K lines and to help interpret the observations of CHROMIS, a new imaging spectrometer at the SST. On a similar vein, 3D simulations were used to study the polarisation of chromospheric lines such as Lyα ( Štěpán et al, 2015;Schmit et al, 2017) and Ca ii 854.2 nm ( Štěpán and Trujillo Bueno, 2016). These studies provide unique insight into the formation mechanism of different spectral lines, are invalu-able for observers, and are a model for successfully understanding future solar observations.…”
Section: Optically-thick Radiative Transfermentioning
confidence: 99%